The Border of Lights Reader Bearing Witness to Genocide in the Dominican Republic - Myers, Megan Jeanette (Amherst College Press, 2021)
Border of Lights, a volunteer collective, returns each October to Dominican-Haitian border towns to bear witness to the 1937 Haitian Massacre ordered by Dominican dictator Rafael Leónidas Trujillo. This crime against humanity has never been acknowledged by the Dominican government and no memorial exists for its victims. A multimodal, multi-vocal space for activists, artists, scholars, and others connected to the BOL movement, The Border of Lights Reader provides an alternative to the dominant narrative that positions Dominicans and Haitians as eternal adversaries and ignores cross-border and collaborative histories. This innovative anthology asks large-scale, universal questions regarding historical memory and revisionism that countries around the world grapple with today.